THU0101 Cardiovascular magnetic resonance imaging characterisation of cardiovascular abnormalities in individuals at risk of developing rheumatoid arthritis. (15th June 2017) - Fent, GJ; Hunt, L; Mankia, KS; Erhayiem, B; Foley, JR; Garg, P; Swoboda, PP; Andrews, J; Greenwood, JP; Emery, P; Plein, S; Buch, MH
Abstract : Background: Inflammation is the primary contributor to excess cardiovascular (CV) disease in rheumatoid arthritis (RA), with evidence of subclinical abnormalities observed even in treatment-naïve, early RA [1]. Preliminary reports suggest citrullinated proteins are present in atherosclerotic plaque [2]. It is unclear whether immunological changes of anti-citrullinated protein antibody (anti-CCP+) positive individuals "at risk" of developing RA are associated with CV abnormality. Objectives: To perform a pilot study to explore whether subclinical CV abnormalities are present in anti-CCP+ individuals at risk of developing RA. Methods: Sixteen consecutive patients with non specific MSK symptoms but no synovitis, detectable anti-CCP antibody and 30 age-matched healthy controls (HC) underwent a multi-parametric 3.0T (Philips Achieva) cardiovascular magnetic resonance (CMR) study. Neither group had any history of CV disease. At-risk individuals were categorised as low and high absolute risk for RA development (<50% and ≥50% respectively) according to a published risk model [3]. CMR post-processing was performed using CVI 42 (Circle Cardiovascular Imaging, Canada). Results: HC and at risk individuals were well matched for baseline characteristics (table 1 ). Aortic strain values (distensibility, strain and stiffness index β) were lower, indicating increased aortic stiffness, in at-risk individuals than HC, numerically most pronounced those classified high risk (table 2). There were no differences in LV mass and function, late gadolinium enhancement, myocardial T1 (measure of myocardial composition) or LV S prime (longitudinal LV systolic function) (table 2). Conclusions: Anti-CCP+ individuals with non-specific MSK symptoms (in particular, a high risk group), exhibit increased aortic stiffness. This suggests presence of CV abnormalities prior to development of RA and implies a role of autoantibody-mediated development of atherosclerosis. These findings warrant further investigation in larger scale studies. References: Erhayiem B et al. Newly diagnosed, treatment-naive patients with rheumatoid arthritis have early abnormalities of vascular and myocardial function. J Cardiovasc Magn Reson 2015;17:P285. Sokolove J et al. Brief report: citrullination within the atherosclerotic plaque: a potential target for the anti-citrullinated protein antibody response in rheumatoid arthritis. Arthritis Rheum 2013;65:1719–24. Rakieh C et al. Predicting the development of clinical arthritis in anti-CCP positive individuals with non-specific musculoskeletal symptoms?: a prospective observational cohort study. Ann Rheum Dis 2015;74:1659–1656. Disclosure of Interest: None declared